Expression of BAF57 in ovarian cancer cells and drug sensitivity. Issue 4 (25th February 2015) - Yamaguchi, Takahiro; Kurita, Tomoko; Nishio, Kazuto; Tsukada, Junichi; Hachisuga, Toru; Morimoto, Yasuo; Iwai, Yoshiko; Izumi, Hiroto
Abstract : The SMARCE1 (SWI / SNF‐related, matrix‐associated, and actin‐dependent regulator of chromatin, subfamily e, member 1) encodes BAF57 protein. Previously, we reported that BAF57 is a predictive marker of endometrial carcinoma. In this study, we investigated BAF57 expression in ovarian cancer cell lines and their sensitivities to cisplatin, doxorubicin, paclitaxel, and 5‐fluorouracil. BAF57 expression was strongly correlated with sensitivities to cisplatin, doxorubicin, and 5‐fluorouracil in 10 ovarian cancer cell lines. Paclitaxel sensitivity was also correlated with BAF57 expression, but without significance. In A2780 ovarian cancer cells, knockdown of BAF57 using specific siRNA increased cell cycle arrest at G1 phase and the sensitivities to these anticancer agents. cDNA microarray analysis of A2780 cells transfected with BAF57 siRNA showed that 134 genes were positively regulated by BAF57, including ATP‐binding cassette, sub‐family G ( WHITE ), member 2 ( ABCG2 ) encoding breast cancer resistance protein (BCRP). We confirmed that knockdown of BAF57 decreased BCRP expression in ovarian cancer cells by Western blot analysis, and that ABCG2 gene expression might be regulated transcriptionally. These results suggested that BAF57 is involved in ovarian cancer cell growth and sensitivity to anticancer agents, and that BAF57 may be a target for ovarian cancer therapy. Abstract : BAF57 expression was strongly correlated with sensitivities to cisplatin, doxorubicin, and 5‐FU in 10 ovarian cancer cell lines. We found that BAF57 might be associated with cell cycle and transport of anti‐cancer agents.